2012
DOI: 10.3389/fonc.2012.00073
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced brain injury: A review

Abstract: Approximately 100,000 primary and metastatic brain tumor patients/year in the US survive long enough (>6 months) to experience radiation-induced brain injury. Prior to 1970, the human brain was thought to be highly radioresistant; the acute CNS syndrome occurs after single doses >30 Gy; white matter necrosis occurs at fractionated doses >60 Gy. Although white matter necrosis is uncommon with modern techniques, functional deficits, including progressive impairments in memory, attention, and executive function h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
414
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 568 publications
(433 citation statements)
references
References 176 publications
(270 reference statements)
13
414
0
6
Order By: Relevance
“…The fact that radiation exposure leads to reduced spine density and, in particular, inhibits the formation of immature filopodia, is consistent with the adverse neurocognitive sequlae documented in brain cancer survivors subjected to cranial radiotherapy (1,34). The persistence of these structural changes coincides with the protracted recovery of the irradiated CNS, and is again consistent with the progressive and irreversible nature of radiation-induced cognitive dysfunction (11,35).…”
Section: Discussionsupporting
confidence: 58%
“…The fact that radiation exposure leads to reduced spine density and, in particular, inhibits the formation of immature filopodia, is consistent with the adverse neurocognitive sequlae documented in brain cancer survivors subjected to cranial radiotherapy (1,34). The persistence of these structural changes coincides with the protracted recovery of the irradiated CNS, and is again consistent with the progressive and irreversible nature of radiation-induced cognitive dysfunction (11,35).…”
Section: Discussionsupporting
confidence: 58%
“…Past work from others and us has shown that irradiation leads to persistent and temporally complex patterns of neuroinflammation (7,21,22). We have shown that transplantation of hNSCs can reduce radiation-induced inflammation to below background levels when assessed 1 or 8 mo after irradiation (5, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Complications of cranial radiation can be classified into three categories based on the timing after exposure to the radiation; acute complication, early delayed complication, and late complication [3]. Vascular injury including large and small vasculopathy related to radiation usually occurs as a delayed complication [4]. A previous report of cranial irradiation in pediatric patients with brain tumor showed that the risk of stroke was 100-fold higher than general pediatric population due to delayed vasculopathy [5].…”
Section: Discussionmentioning
confidence: 99%